2017
DOI: 10.1515/jomb-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote Hemoglobin G-Coushatta as the Cause of a Falsely Decreased Hemoglobin A1C in an Ion-Exchange HPLC Method

Abstract: SummaryGlycated hemoglobin (HbA1c) is used for the assessment of glycemic control in patients with diabetes. The presence of genetic variants of hemoglobin can profoundly affect the accuracy of HbA1c measurement. Here, we report two cases of Hemoglobin G-Coushatta (HBB:c.68A>C) variant that interferes in the measurement of HbA1c by a cationexchange HPLC (CE-HPLC) method. HbA1c was measured by a CE-HPLC method in a Tosoh HLC-723 G7 instrument. The HbA1c levels were 2.9% and 4%. These results alerted us to a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The interindividual variation in HbA1c, defined as the glycation gap, is not attributable to mean blood glucose values and has been indicated to be associated with diabetic nephropathy ( 3 , 11 ). Several studies have described low HbA1c levels in patients with Hb variants ( 9 , 12 , 13 ). According to the laboratory test data obtained for the patient of the present study, numerous factors that may lead to low HbA1c levels were excluded, except for Hb variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interindividual variation in HbA1c, defined as the glycation gap, is not attributable to mean blood glucose values and has been indicated to be associated with diabetic nephropathy ( 3 , 11 ). Several studies have described low HbA1c levels in patients with Hb variants ( 9 , 12 , 13 ). According to the laboratory test data obtained for the patient of the present study, numerous factors that may lead to low HbA1c levels were excluded, except for Hb variants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that this variant usually leads to underestimation of HbA1c and HbA variants constitute a well-known cause of analytical interference in the measurement of HbA1c levels ( 7-10 ). One of these studies suggested that the Hb G-Coushatta variant affected the determination of HbA1c levels, with the ion-exchange HPLC method measuring an HbA1c level that was 45% lower than that obtained by the immunoturbidimetric assay method ( 9 ). Thus, it may be concluded that the Hb G-Coushatta variant is the most likely cause of the HbA1c measured by HPLC appearing normal, which was clearly inconsistent with the clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation